The shadow of Perseus : a novel - Heywood, Claire (Dutton, 2023)
"Nationally bestselling author of Daughters of Sparta Claire Heywood returns with an imaginative and female-centered reinterpretation of the myth of the great hero Perseus, told through the voices of three women who are sidelined in the traditional version - his mother Danae, his trophy Medusa, and his wife Andromeda - but whose viewpoints reveal a man who is not, in fact, a hero at all"--